«Lire dans les cassures»: the production of knowledge in Faujas de Saint-Fond’s Recherches sur les volcans éteints du Vivarais et du Velay (1778) - McCallam, David (Diciottesimo Secolo, 2025)
In his Recherches sur les volcans éteints du Vivarais et du Velay, the French geologist Barthélemy Faujas de Saint-Fond (1741-1819) engages in innovative fieldwork in his quest to confirm the volcanic nature of basalt in the extinct volcanoes of south-eastern France. Following Jean-Etienne Guettard (1715-1786) and Nicolas Desmarest (1725-1815), Faujas conceives of ‘nature’ as both a site of knowledge and an autonomous agency deploying its own practices of production. As a field chemist, Faujas is similarly at once a producer of knowledge and merely one of its organic instruments. As his primary materials are prismatic basalt columns, Faujas’s knowledge production privileges rock form over rock formation – sectioning rocks physically and landscapes diagrammatically. This constitutes an epistemological extraction modelled on the material extraction of rocks identified primarily by their crystal structures. Yet this empirical production of knowledge is further inflected by ethnographic reflection (travel narrative), aesthetic stylization (illustrations) and its re-inscription into local, national and European networks of correspondence.